Common mental disorders among women and its social correlates in an urban marginalized populace in South India. (November 2022) - Nair, Aiswarya R; Shivanna, Yeshvanth Kumar Gubbi; Illimoottil, Jesson Paulson; Rachana, Arun; Mahasampath, Gowri S; Abraham, Sunil; Kurian, Suja
Background: Common mental disorders (CMD) cause a range of health, social and economic burden, and disorders like depression and anxiety are more prevalent among women. Prevalence and factors contributing to increased vulnerability for CMDs have regional variation. Identification of factors contributing to the vulnerability is essential to both psychiatric epidemiology and in addressing mental health challenges in the community. Methods: This cross-sectional study aimed at understanding the burden of CMD and its association with social determinants of mental health. Women hailing from urban slum attending the outpatient family care facility for their medical problems constituted the sample. Data was collected using a clinical research form with variables such as sociodemographic profile, health profile, and psychosocial profile. The questionnaire had specific questions on indicators of poverty, certain stressors, and support system. Presence of CMD was assessed using Clinical Interview Schedule-Revised (CIS-R), a standard tool for CMD research in primary care settings. A cut off score of 12 and above was considered for detecting CMD. Research ethical principles were adhered to and data was analyzed using SPSS 21.0. Results: Among 172 women, 77 (44.8%) were diagnosed to have CMDs. Univariate analysis revealed a significant association between age, marital status, living arrangement, educational level, difficulty with buying food, presence of debt, chronic medical illness, husband's alcohol use, marital satisfaction, experiencing abuse, family support, religious participation, and a diagnosis of CMD. Multivariate analysis showed high burden with nuclear family arrangement, difficulty to buy food, experiencing abuse and, low burden with higher educational level, family support, and religious participation. Conclusion: Considering the high prevalence and the treatment gap of CMDs in primary setting, family-physician should be sensitized for detection and management of CMDs. Social interventions targeting poverty, women's education and empowerment, and support system are likely to decrease the burden of CMDs in this population.